Caribbean Report 16-05-1990 - Whitehorne, Pat (anchor); Caroit, Jean Michel (correspondent); Hector, Tim (interviewee); Stainer, Robin (analyst); Ashford, Kevin (correspondent); McGowan, Michael (interviewee); Porter, Adrian (correspondent); Norton, Michael (correspondent) (The British Broadcasting Corporation, 1990)
Elections day in the Dominican Republic and amongst the first to vote was Juan Bosch, the frontrunner in the election race according to all the polls. The morning period saw long lines at the polling stations without any major incidence reported. Secondly, Vere Bird Sr., the Prime Minister of Antigua, met with his Cabinet and they agreed on the terms of reference for the Commission of Enquiry to investigate the arms scandal in Antigua. Whilst the meeting was in progress, the two opposition parties, the UNDP and the ACLM, joined forces to protest outside the prime minister’s office. Following the Financial News, the Green Parties in the European Parliament failed to block parliamentary approval of the fourth Lome agreement on trade and aid between the EEC and the ACP group of countries. The report concludes with the announcement by the United States that it has resumed official aid to Haiti after a one-year suspension due to evidence of political fraud in the national elections and continuing abuse of human rights.
1. Headlines (00:00-00:36)
2. Opposition leader in the Dominican Republic warns of confusion in the voting procedures. Jean Michel Caroit reports from Santo Domingo (00:37-02:27)
3. Antiguan Cabinet agrees on the terms of reference for the arms scandal enquiry. Comments from Tim Hector, leader of the Antigua Caribbean Liberation Movement (02:28-04:33)
4. Financial News. Robin Stainer, Commodity Analyst, comments on the price of cocoa on the world market (04:34-06:08)
Keywords: Elections -- Dominican Republic; Elections -- Statistics -- Dominican Republic; Arms transfers -- Antigua; Economic assistance -- Haiti -- United States; Lome IV -- ACP-Group; Green Parties -- Europe